Induction of Type-C RNA Virus by Cycloheximide: Increased Expression of Virus-Specific RNA - Aaronson, Stuart A. (1974)
Mouse cells contain the genetic information for multiple endogenous type-C RNA viruses. The mechanisms by which the cell controls expression of these naturally integrated viruses are not yet known. Recently, chemicals that inhibit protein synthesis have been shown to induce a specific type-C virus at high frequency from BALB/c mouse embryo cells. In the present studies, virus activation in response to a representative translational inhibitor, cycloheximide, is demonstrated to be transient, with virus release primarily occurring within the first 12-24 hr following drug exposure. Analysis of virus-specific RNA in cells by molecular hybridization revealed an absolute increase in viral RNA concentration in cycloheximide-treated cells. This was blocked by simultaneous exposure of the cells to actinomycin D. Further, inhibition of RNA synthesis during but not subsequent to cycloheximide exposure prevented virus activation. These findings show that virus induction by cycloheximide requires de novo RNA synthesis during but not after drug exposure and suggest that the required RNA species may be that of the virus itself. The present results are consistent with the hypothesis that translational inhibitors prevent synthesis of a labile protein whose normal action is to inhibit viral RNA transcription or to cause degradation of viral RNA.